NUMERICAL STUDY: COMPARISON THE EFFECT OF RATIO LENGTH AND DIAMETER GUIDE VANE OF AIR FLOW ON OUTLET DUCTING - Fajar Anggara (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2020)
Guide vane has an important role for conditioning flow pattern of fluid velocity. With the configuration of axial turbine blade, the flow pattern near wall must have the highest velocity. As such that intention, this research is conducted to compare between the effect of dimension ratio of length and diameter of guide vane using ANSYS FLUENT 17. The dimension ratio of guide vane has been divided into two types with each of types has three variations. Type 1 is ratio of length that having variation A, B and C, whilst type 2 is ratio of diameter with D, E and F variations. The result shows that variation B and F produces the highest velocity. Because the effect of acceleration on variation B is maximum so that it increases the velocity, while on variation F has the smallest angle of guide vane that would reduce the drag force.